2014
DOI: 10.1021/bi500285t
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Small Laccases fromStreptomycesin Lignin Degradation

Abstract: Laccases (EC 1.10.3.2) are multicopper oxidases that can oxidize a range of substrates, including phenols, aromatic amines, and nonphenolic substrates. To investigate the involvement of the small Streptomyces laccases in lignin degradation, we generated acid-precipitable polymeric lignin obtained in the presence of wild-type Streptomyces coelicolor A3(2) (SCWT) and its laccase-less mutant (SCΔLAC) in the presence of Miscanthus x giganteus lignocellulose. The results showed that strain SCΔLAC was inefficient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 62 publications
1
128
0
Order By: Relevance
“…This phenomenon has been observed for R. jostii RHA1 DyPB [9], and also for bacterial laccases from Streptomyces coelicolor and S. viridosporus T7A [24], and represents a significant challenge for the use of these enzymes in vitro for lignin depolymerisation, though this phenomenon is generally not observed in living systems, so there may be mechanisms to combat this phenomenon in vivo.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This phenomenon has been observed for R. jostii RHA1 DyPB [9], and also for bacterial laccases from Streptomyces coelicolor and S. viridosporus T7A [24], and represents a significant challenge for the use of these enzymes in vitro for lignin depolymerisation, though this phenomenon is generally not observed in living systems, so there may be mechanisms to combat this phenomenon in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…Dimeric -aryl ether lignin model compounds have been frequently used to study the action of fungal lignin-oxidising enzymes [23], and bacterial DyPs [9,10] and laccases [24]. TfuDyP was incubated with guaiacylglycerol--guaiacyl ether (1) at 1.6 mg/ml concentration in 100 mM sodium acetate buffer pH 6.0 in the presence of 1 mM hydrogen peroxide.…”
Section: Oxidation Of -Aryl Ether Lignin Model Compoundmentioning
confidence: 99%
“…Peroxidase activities are reported in bacterial taxa, such as Firmicutes, Proteobacteria, Actinobacteria and Acidobacteria (155,156). Moreover, actinomycetes, which are soil bacteria, are able to grow like fungi and have similar ecological niche, and can produce peroxidases for lignin degradation (154,157). The first secreted extracellular lignin peroxidase was produced by Streptomyces viridosporus T7A (158).…”
Section: Peroxidasementioning
confidence: 99%
“…This problem has been encountered using fungal lignin peroxidase [12][13][14] and laccase enzymes [15,16] and with bacterial Dyp peroxidase [17] and laccase [18] enzymes, and is also encountered in chemocatalytic valorisation of lignin, where a high molecular weight char is observed alongside depolymerised products [1]. Kirk & Farrell commented on this problem in their review of microbial lignin oxidation in 1987, noting that polymerisation of lignin is not prominent in vivo, therefore they suggested that phenoxy radical intermediates "are reduced back to the phenols by an undiscovered enzyme and/or mechanism that prevents polymerization" [19].…”
Section: Introductionmentioning
confidence: 99%